2011
DOI: 10.1007/s10494-011-9361-0
|View full text |Cite
|
Sign up to set email alerts
|

Gas Flow Measurements by 3D Particle Tracking Velocimetry Using Coloured Tracer Particles

Abstract: This work describes an original approach for 3D Particle Tracking Velocimetry (3D PTV), applicable also for gaseous flows and based on tracer particles of different colours. On the images acquired by several cameras, tracer particles are handled by colour recognition and 3D localisation. Then, the PTV tracking algorithm rebuilds the trajectories of the tracer particles using a criterion of Minimum Acceleration. Theoretical and numerical calculations are first presented to demonstrate that the employed coloured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…According to Kallio and Stock (1992), the tracer particle is suitable when the Stokes number . Recently, Tarlet et al (2011) and Burgmann et al (2001) reported that for a Stokes number , the deviation of the tracer particle is negligible.…”
Section: Tracking Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Kallio and Stock (1992), the tracer particle is suitable when the Stokes number . Recently, Tarlet et al (2011) and Burgmann et al (2001) reported that for a Stokes number , the deviation of the tracer particle is negligible.…”
Section: Tracking Indicatorsmentioning
confidence: 99%
“…2. Their size and density should fulfill conditions avoiding sedimentation and inertial effects (Tarlet et al (2011)). 3.…”
Section: Tracking Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The computation of trajectories is described in detail in a separate publication [25]. Figure 9 demonstrates the ability to obtain PTV data within the whole three-dimensional volume of observation around three winglets (Case 1).…”
Section: Experimental Determination Of the Localization Uncertaintymentioning
confidence: 99%